The extent of the use of social networking sites by the students of the Faculty of education (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The current study aimed to identify the extent to which students of the Faculty of Education at Tishreen University use social media in the educational process related to their research seminars and graduation projects, according to the variables of gender and academic specialization. The researcher designed for this purpose a questionnaire consisting of (20) items distributed on four main axes, distributed on a random sample, consisting of (339) male and female students in the College of Education from different academic years, and from various specializations. The results of the study showed that the extent of the use of the students of the College of Education for social networking sites in the educational process related to their research seminars and graduation projects is large, as the relative weight of use (80%). It was also found that there was no difference between the average scores of students of the College of Education with regard to the use of social networking sites in the educational process, according to the variables of sex and academic specialization. In addition to the presence of a set of proposals submitted by students to facilitate the use of social networking sites in the educational process, namely: Providing internet service at the university, and facilitating communication with members of the educational body.   هدفت الدّراسة الرّاهنة التعرّف إلى مدى استخدام طلاب كليّة التربيّة بجامعة تشرين لمواقع التّواصل الاجتماعيّة في العمليّة التعليمية المتعلّقة بحلقاتهم البحث ومشاريع التخرّج، وفقاً لمتغيري الجنس والتّخصّص الدّراسي. وصمّمت الباحثة لهذا الهدف استبانة مؤلّفة من (20) بنداً موزّعاً على أربعة محاور رئيسة، وزّعت على عيّنة عشوائية، مكوّنة من (339) طالباً وطالبةً في كلية التربية من مختلف السّنوات الدّراسيّة، ومن مختلف الاختصاصات. وقد أظهرت نتائج الدّراسة، أنّ مدى استخدام طلاب كلية التربية لمواقع التواصل الاجتماعية في العملية التعليمية المتعلّقة بحلقاتهم البحث ومشاريع التخرّج كبيراً؛ إذ بلغ الوزن النّسبي للاستخدام (80%). وتبيّن أيضاً عدم وجود فرق بين متوسّطي درجات طلبة كليّة التّربية فيما يتعلّق باستخدام مواقع التّواصل الاجتماعيّة في العمليّة التّعليمية، تبعاً لمتغيّري الجنس والتّخصّص الدّراسي. إضافةً إلى وجود مجموعة من المقترحات قدّمها الطّلبة لتسهيل استخدام مواقع التّواصل الاجتماعيّة في العمليّة التعليميّة، وهي: توفير خدمة الانترنت في الجامعة، وتسهيل التّواصل مع أعضاء الهيئة التّعليميّة.